Gender and Number Agreement in the Oral Production of L1 Arabic Among Bilingual Arab-Americans - Al-shammari, khalid (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Bilingualism means the ability to communicate in two languages and in some cases,with better skills in one language versus the other. Most bilinguals have one language that ismoredominant than the other due to sequential acquisition.That is, the dominant language is used in everyday communication and in school. Heritage languages are immigrant languages